Virtual geo-hazard monitoring and asset management system (VIGMAS) - Omar R.C.; Taha H.; Roslan R.; Baharuddin I.N.Z.; Fared M.M.; Hashim W.S.W. (International Association of Lowland Technology, 2023)
Asset management; Data visualization; Decision making; Geographic information systems; Hazards; Health risks; Image processing; Information use; Mapping; Monitoring; Remote sensing; Risk management; 4D visualization; Asset management systems; Management planning; Management programs; Meteorological parameters; Near-real time; Remote sensing technology; Satellite image processing; Information management; environmental monitoring; geological hazard; GIS; hazard assessment; image processing; mapping; risk assessment; satellite imagery; terrain; virtual reality; visualization